Reflections on Forme dell'addio by Ernesto Napolitano (De Musica, 2024)
This article presents an extended commentary on Ernesto Napolitano’s book, Forme dell’addio on the late music of Gustav Mahler. Following the pathway in the Mahlerian world that Napolitano proposes, the article discusses his key points related to Mahler’s early modernism: a) tendency to abstraction; b) anti-subjectivism; c) anti-anthropocentrism; d) objectivity and disenchantment; e) Mahlerian narrativity as ‘modern epics’, according to Moretti’s theory (1994); f) comparison between the late Mahlerian works and those of the Wunderhorn years. First, by discussing these points the article suggests a stronger link between the late Mahlerian style and that of the Wunderhorn years than what Napolitano presents. Then, the article enlarges the theoretical and hermeneutical range of anti-anthropocentrism, which Napolitano limits Mahler’s music narrativity but that can be a reading key of this musicologist’s findings on the Eighth Symphony and Das Lied von der Erde, Lastly, starting from Napolitano’s analysis of Mahler’s Tenth Symphony, the author of the present article implies a stronger application of the paradigm of modern epics to this symphony. As an example of this direction of research, he then proposes outcomes from his previous articles on this symphony (Pinto 2019, 2020).